Partial Fiscal Decentralization and Sub-National Government Fiscal Discipline: Empirical Evidence from OECD Countries - Zareh Asatryan; Lars P. Feld; Benny Geys (Center for Economic Studies and ifo Institute (CESifo), 2015)
Recent theoretical research suggests that financing sub-national governments' expenditure out of own revenue sources is linked to more responsible budgeting, because the financial implications of spending decisions then are internalized within a jurisdiction. We test this proposition empirically on a sample of 23 OECD countries over the 1975-2000 period, and find evidence in line with the hypothesis that greater revenue decentralization (measured as sub-national governments' share of own source tax revenues in general government tax revenue) is associated with improved sub-national government budget deficits/surpluses. This finding is cross-validated with a novel, independent dataset consisting of all 34 OECD member states from 2002 to 2008.
Keywords: H62; H71; H77; E61; 330; fiscal federalism; revenue autonomy; budget deficits